PENGGUNAAN MAKROZOOBENTOS SEBAGAI BIOASSESSMENT ANAK SUNGAI BRANTAS - Mohammad Mirwan; Erina Citra Pratiwi Anik Setyowati (EnviroUS, 2022)
The Mangetan Canal River is a river with a length of ± 36.3 kilometers which is often used as a place for waste to end up resulting in a decrease in the quality of the water (Ahmad et al, 2016). In this study, testing was carried out at 4 stations in the morning and evening for 4 weeks. The result is for parameters of temperature, pH, salinity meet the quality standards. For the DO parameter, COD has not met the quality standard. For brightness parameters only in weeks 1 and 2 that meet the quality standard. The composition of macrozoobenthos at week 1 to week 4 found 9 species belonging to 5 classes, namely Oligochaeta, Diptera, Gastropods, Celeoptera and Hirudinea. The density of macrozoobenthos showed the results of 15-1980 individuals/m2 per station during the study. For the calculation of IP and BMWP-ASPT, it was found that manganese was heavily polluted to very heavily polluted with the BMWP-ASPT method and the results were lightly polluted with the Pollution Index (IP) method. The results of the correlation between the Pollution Index and BMWP-ASPT are strongly correlated between variables (X) and (Y). The recommendation of this research is that sampling should be done in real time and it is necessary to develop other parameters that must be investigated that can affect the biota in the waters